Identification of quantitative trait loci and candidate genes for primary metabolite content in strawberry fruit - Pott, DM; Cruz-Rus, E; Miranda, L; Medina-Minguez, JJ; Valpuesta-Fernández, Victoriano; Fernie, AR; Sanchez-Sevilla, JF; Osorio-Algar, Sonia; Amaya, I (My University, 2019)
Improvement of nutritional and organoleptic quality of fruits is a key goal in current strawberry breeding programs. The ratio of sugars to acids is a determinant factor contributing to fruit liking, although different sugars and acids contribute in varying degrees to this complex trait. A segregating F1 population of 95 individuals, previously characterized for several fruit quality characters, was used to map during 2 years quantitative trait loci (QTL) for 50 primary metabolites, L -ascorbic acid (L-AA) and other related traits such as soluble solid content (SSC), titratable acidity (TA), and pH. A total of 133 mQTL were detected above the established thresholds for 44 traits. Only 12.9% of QTL were detected in the 2 years, suggesting a large environmental influence on primary metabolite content. An objective of this study was the identification of key metabolites that were associated to the overall variation in SSC and acidity. As it was observed in previous studies, a number of QTL controlling several metabolites and traits were co-located in homoeology group V (HG V). mQTL controlling a large variance in raffinose, sucrose, succinic acid, and L-AA were detected in approximate the same chromosomal regions of different homoeologous linkage groups belonging to HG V. Candidate genes for selected mQTL are proposed based on their co-localization, on the predicted function, and their differential gene expression among contrasting F1 progeny lines. RNA-seq analysis from progeny lines contrasting in L-AA content detected 826 differentially expressed genes and identified Mannose-6-phosphate isomerase, FaM6PI1, as a candidate gene contributing to natural variation in ascorbic acid in strawberry fruit
Keywords: Fresas; strawberry; fruit; quantitative trait loci; quality; metabolites